Konsep Desain Taman Sekolah Dasar di Desa Pering dalam Akomodasi Psikomotorik Anak Usia Dini - Saputra, Kadek Edi; Dharmadiatmika, I Made Agus; Megisterina, Megisterina (Jurnal Arsitektur Lansekap; Vol. 10, No. 2 Oktober 2024, 2024)
Elementary School Garden Design Concept in Pering Village in Accommodating Early Childhood Psychomotor Skills . The development of children's psychomotor skills is crucial to raising early childhood IQ. Many young children are restricted to indoor activities like playing with cellphones, sleeping, and other activities that don't require physical movement due to rapidly evolving technology and an unsupportive environment. By addressing these issues, researchers at Elementary School 5 Pering attempt to create aesthetically pleasing outdoor areas that enhance young children's psychomotor abilities. Through on-site case discussions and direct design proposals for research challenges and objectives, this study employs a qualitative research methodology. placing a strong emphasis on the spiritual and moral, physical, intellectual, emotional, and artistic facets of life. The fundamental idea or concept used in the design concept is active and continuous, which refers to the analysis and issues researched about the accommodation of early childhood psychomotor skills. Comprehensive concepts that are used to the design to promote early childhood psychomotor skills are filled with active and continuous elements. A site layout that accommodates the theme—active and continuous—is the study's end product.